BRIDGING DIFFERENCES FOR BETTER MENTORING : lean forward, learn, leverage;lean forward, learn, leverage. - FAIN, LISA;ZACHARY, LOIS J. (BERRETT-KOEHLER, 2020)
This first comprehensive guide to helping mentors and mentees bridge gaps between and among cultures--a growing issue in today's diverse workplace--is coauthored by the founder and CEO of the Center for Mentoring Excellence. As the workplace has become more diverse, mentoring has become more challenging. Mentors and mentees may come from very different backgrounds and have limited understanding of each other's cultures and outlooks. But mentoring remains the most powerful tool for creating meaningful relationships, furthering professional development, and increasing engagement and retention. Younger workers and emerging leaders in particular are demanding it. Lisa Z. Fain and Lois J. Zachary offer a timely, evidence-based, practical guide for helping mentors develop the level of cultural competency needed to bridge differences. Firmly rooted in Zachary's well-known four-part mentoring model, the book uses three fictional scenarios featuring three pairs of diverse mentors and mentees to illustrate how key concepts can play out in real life. It offers an array of accessible tools and strategies designed to help you increase your self-awareness and prepare you to embrace and leverage differences in your mentoring relationships. But beyond tips and techniques, Fain and Zachary emphasize that authenticity is the key--the ultimate purpose of this book is to help the mentor and mentee make a genuine connection and learn from each other. That's when the magic really happens.
Keywords: Mentoring in business.; Diversity in the workplace.; Intercultural communication.; Mentorat dans les affaires.; Multiculturalisme en milieu de travail.; Diversity in the workplace; Intercultural communication; Mentoring in business